Health and Aging before and after Retirement - Ana Lucia Abeliansky; Holger Strulik (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate health and aging before and after retirement for specific occupational groups. We use five waves of the Survey of Health, Aging, and Retirement in Europe (SHARE) and construct a frailty index for elderly men and women from 10 European countries. Occupational groups are classified according to low vs. high education, blue vs. white collar color, and high vs. low physical or psychosocial job burden. Controlling for individual fixed effects, we find that, regardless of the used classification, workers from the first (low status) group display more health deficits at any age and accumulate health deficits faster than workers from the second (high status) group. We instrument retirement by statutory retirement ages (“normal” and “early”) and find that the health of workers in low status occupations benefits greatly from retirement, whereas retirement effects for workers in high status occupations are small and frequently insignificant. We also find that workers from low status occupations always have higher health deficits, i.e. we find evidence for an occupational health gradient that widens with increasing age, before and after retirement.
Keywords: I10; I19; J13; 330; health deficits; occupation; retirement; frailty index; Europe